Effect of Bone Plugging at the Distal Femoral Drilled Hole in Total Knee Arthroplasty on Early Clinical Outcomes - Tanasubsinn, MD, Natee; Tanavalee, MD, Aree; Boonyanuwat, MD, Wittawat; Ngarmukos, MD, Srihatach (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: Bone plugging at the intramedullary (IM) femoral drilled hole in total knee arthroplasty (TKA) is performed with expectation to decrease blood loss. We hypothesized that the retained blood in IM canal may affect postoperative thigh & leg heaviness (TLH), quadriceps peak torque (QPT) and immediate clinical outcomes. Methods: Eighty-one patients undergoing unilateral TKA using IM femoral bone cut were randomly divided into 2 groups; group I: drilled hole plugged with a bone graft, and group II: drilled hole was left open. Postoperatively, clinical parameters were sequentially evaluated until 12 weeks. Results: There were 41 knees in group I and 40 knees in group II. Preoperative demographic data of both groups were not different. There was no difference in blood collected from drain and transfusion rate. The TLH similarly changed from severe grade at 2 weeks to none and mild grade at 12 weeks. The QPT was similarly decreased by 38% at 2 weeks, and improved to preoperative level at 12 weeks. There were no differences in visual analog scale (VAS), range of motion (ROM), Western Ontario and McMaster Universities Arthritis Index (WOMAC) and Knee Society System (KSS) scores between both groups. Conclusion: Comparing between plugging or unplugging femoral IM hole in TKA, the present study found no difference in blood loss, and retained blood in IM canal did not have effect on TLH, QPT and other immediate clinical outcomes. Plugging of the femoral IM hole provided no harm or advantages which could be performed according to surgeon’s preference.